Effect of an Intervention Package and Teamwork Training to Prevent Healthcare Personnel Self-contamination During Personal Protective Equipment Doffing. (13th September 2019) - Andonian, Jennifer; Kazi, Sadaf; Therkorn, Jennifer; Benishek, Lauren; Billman, Carrie; Schiffhauer, Margaret; Nowakowski, Elaine; Osei, Patience; Gurses, Ayse P; Hsu, Yea-Jen; Drewry, David; Forsyth, Ellen R; et al.
Abstract: Background: More than 28 000 people were infected with Ebola virus during the 2014–2015 West African outbreak, resulting in more than 11 000 deaths. Better methods are needed to reduce the risk of self-contamination while doffing personal protective equipment (PPE) to prevent pathogen transmission. Methods: A set of interventions based on previously identified failure modes was designed to mitigate the risk of self- contamination during PPE doffing. These interventions were tested in a randomized controlled trial of 48 participants with no prior experience doffing enhanced PPE. Contamination was simulated using a fluorescent tracer slurry and fluorescent polystyrene latex spheres (PLSs). Self-contamination of scrubs and skin was measured using ultraviolet light visualization and swabbing followed by microscopy, respectively. Doffing sessions were videotaped and reviewed to score standardized teamwork behaviors. Results: Participants in the intervention group contaminated significantly fewer body sites than those in the control group (median [interquartile range], 6 [3–8] vs 11 [6–13], P = .002). The median contamination score was lower for the intervention group than the control group when measured by ultraviolet light visualization (23.15 vs 64.45, P = .004) and PLS swabbing (72.4 vs 144.8, P = .001). The mean teamwork score was greater in the intervention group (42.2 vs 27.5, P < .001). Conclusions: An intervention package addressing the PPE doffing task, tools, environment, and teamwork skills significantly reduced the amount of self-contamination by study participants. These elements can be incorporated into PPE guidance and training to reduce the risk of pathogen transmission. Abstract : An intervention package that addressed components of the task, tools, environment, and teamwork skills during personal protective equipment (PPE) doffing significantly reduced the amount of self-contamination by study participants. These elements can be incorporated into PPE guidance and training to prevent pathogen transmission.